2013
DOI: 10.7860/jcdr/2013/4878.2941
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprolactinaemia and its Comparision with Hypothyroidism in Primary Infertile Women

Abstract: Aim and Objective: To study the serum prolactin levels and the serum TSH in primary infertile females. Material and Method:In this study, we investigated thirty women who were diagnosed cases of primary infertility, who attended the Biochemistry Department, Sir JJ Group of Hospitals, Mumbai, India, for hormonal evaluations. Thirty fertile women with similar ages were enrolled as the controls. The status of the thyroid dysfunction and the levels of serum prolactin were reviewed in infertile women and in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 9 publications
6
12
0
Order By: Relevance
“…This is similar to observations made in a study by Sharma et al, [18] and Turankar et al, [19]. A significant positive correlation between TSH and prolactin levels in subjects enrolled in the study (r = 0.285, p<0.05) was observed.…”
Section: Referencessupporting
confidence: 92%
See 1 more Smart Citation
“…This is similar to observations made in a study by Sharma et al, [18] and Turankar et al, [19]. A significant positive correlation between TSH and prolactin levels in subjects enrolled in the study (r = 0.285, p<0.05) was observed.…”
Section: Referencessupporting
confidence: 92%
“…Evidence from experimental and clinical studies have suggested a close relationship between the hypothalamic -pituitary -ovarian axis (HPO) and the hypothalamic -pituitary -thyroid axis (HPT) [19]. This is because, the specific thyroid hormone receptors at the ovarian level may regulate the influence of estrogens as well as reproductive function the at higher levels of the HPT axis thereby integrating the reciprocal relationship between these two major endocrine axes [22].…”
Section: Referencesmentioning
confidence: 99%
“…[13][14][15] In our study, we found that TSH level is significantly higher among infertile cases than the control subjects. This finding is validated by the study done by Sridevi and Sandhya Rani [16] and Turankar et al, [2] who found that hypothyroidism is a more common thyroid disorder among infertile female subjects. Clinical and experimental studies have stated an interrelationship between the hypothalamic-pituitary-thyroid axis and the hypothalamic-pituitary-ovarian axis.…”
Section: Discussionsupporting
confidence: 78%
“…12 In a similar study Sharma et al, investigated prolactin and TSH levels in primary and secondary infertile women and determined galactorrhea in 15% of the subjects. 13 In addition, serum prolactin levels were measured as 79.40±56.59 ng/ml in hyperprolactinemic women; however, they reported no statistically significant difference in the levels of prolactin between the women with primary and secondary infertility.…”
Section: Discussionmentioning
confidence: 99%